An Unusual Complication of Congenital Diaphragmatic Hernia - Tan, E Tian; Sloan, Keren; Lakhoo, Kokila (European Journal of Pediatric Surgery Reports, 2017)
A term newborn was referred to our unit with a postnatal diagnosis of a right-sided congenital diaphragmatic hernia (CDH). She was managed with high-frequency oscillatory ventilation, inotropic support, and nitric oxide, with planned surgical repair when she was medically optimized. On day 6 of life, there was an acute deterioration causing difficulty maintaining adequate ventilation and the infant requiring increasing analgesia and paralysis, especially during abdominal examination. A repeat X-ray showed distended bowel loops in the right hemithorax when compared with previous films raising suspicion of bowel obstruction. The infant proceeded to emergency laparotomy in the neonatal intensive care unit. She was found to have a right-sided Bochdalek (posterolateral) defect. The entire small bowel was within the thoracic cavity and appeared dusky secondary to obstruction caused by compression of a herniated right liver lobe against the hernia defect. Bowel perfusion improved after reduction and a BioDesign patch was used to repair the defect. The infant went on to have a straightforward recovery and was transferred to her local hospital for ongoing care on day 17. Bowel obstruction is an uncommon complication in the perinatal period in infants with CDH. A high index of suspicion for bowel compromise is needed in neonates who deteriorate acutely after a period of stabilization. Imaging should be obtained as soon as possible and early surgical intervention may be life-saving.
Keywords: congenital diaphragmatic hernia; complications; gastrointestinal; obstruction; neonatal; surgery